Implementation of Event-Driven Architecture in Soil Moisture Sensor Data Transmission Based on Master–Slave - Cut Chairunnisa Maulidia; Hafiz Muhardi; Uray Ristian; Nirsal Nirsal; Idawati Idawati (Digital Innovation, 2026)
The decline in chili crop productivity is partly caused by Soil Moisture that is not properly monitored. Manual monitoring is considered less effective, while IoT systems with periodic data transmission tend to be inefficient. This study develops a Soil Moisture monitoring system based on an Event-Driven master–slave architecture using four ESP32 devices. Three act as slaves connected to Soil Moisture sensors, and one serves as the master responsible for data transmission. The Event-Driven method applies two mechanisms: Batch Update every 5 minutes under normal conditions and Immediate Alert when moisture values fall outside the ideal range of 50–70%. System performance is compared with a non-Event-Driven method based on QoS parameters: delay, jitter, payload, and the number of data packets. Testing is conducted through four scenarios, each lasting one hour. Results show that the Event-Driven system is more efficient. The average delay and jitter are 547.35 ms and 557.05 ms, lower than the non-Event-Driven system (3,340.73 ms and 1,755.71 ms). In addition, fewer packets are sent with larger payloads. Although it does not yet meet the TIPHON standard, this method can transmit data immediately during significant changes while reducing the number of transmitted packets.